Hubungan Stres Akademik dengan Keluhan Migrain pada Mahasiswa - Rumuat, Jennifer Telly; Rantepadang, Andreas (Nutrix Journal, 2023)
Migraine is a neurological disease with moderate to severe pain intensity. Migraine complaints can be triggered by several trigger factors, one of which is stress. Academic stress is pressure from a subjective perspective on academic conditions. The purpose of this study was to determine the relationship between academic stress and migraine complaints of students. The design used in this research is a descriptive correlation with a cross-sectional approach. The sample in this study amounted to 45 students with a sampling technique that is purposive sampling. The result showed that 25 students (55,6%) felt severe stress and 20 (44,4%) students felt moderate stress, 35 students (77,8%) did not feel migraine complaints and 10 students (22,2%) felt migraine complaints, and there was a significant relationship between academic stress and migraine complaints with p-value =0,047. The value of r = -0,297 which means the correlation between the two variables is weak and has a negative direction. Recommendations for nursing students can maintain activities that can reduce migraine complaints such as not consuming foods containing glutamate or tyramine, For future researchers, it is advisable to research different variables and add more samples. Keyword: Academic Stress, Migraine Complaints Abstrak Migrain adalah penyakit neurologis dengan intensitas nyeri sedang hingga berat. Keluhan migrain dipicu oleh beberapa faktor pencetus, salah satunya stres. Stres akademik merupakan tekanan dari perspektif secara subjektif terhadap kondisi akademik. Tujuan dari penelitian ini adalah untuk mengetahui hubungan antara stres akademik dengan keluhan migrain pada mahasiswa. Desain penelitian yang digunakan adalah deskriptif korelasi dengan pendekatan cross sectional. Sampel dalam penelitian ini berjumlah 45 mahasiswa dengan teknik sampling purposive sampling. Hasil penelitian didapati ada 25 mahasiswa (55,6%) merasakan stres berat dan 20 (44,4%) mahasiswa merasakan stres sedang, 35 (77,8%) mahasiswa tidak merasakan keluhan migrain dan 10 mahasiswa (22,2%) merasakan keluhan migrain, serta terdapat hubungan yang signifikan antara stres akademik dengan keluhan migrain dengan nilai p-value =0,047. Nilai r =-0,297 yang berarti korelasi hubungan kedua variabel lemah dan memiliki arah negatif. Rekomendasi bagi mahasiswa keperawatan dapat mempertahankan kegiatan-kegiatan yang dapat mengurangi keluhan migrain seperti tidak mengkonsumsi makanan yang mengandung glutamate atau tyramine. Bagi peneliti selanjutya, diharapkan dapat meneliti tentang variabel yang berbeda dan menambahkan jumlah sampel lebih banyak. Kata kunci : Keluhan Migrain, Stres Akademik